Negotiating modernity and the new nationhood in Iban popular song lyrics in 1960s-1970s - Lim, Connie Keh Nie; Yow, Chong Lee; Anna, Durin; Alexander, Chelum (Human Resource Management Academic Research Society (HRMARS), 2012)
Iban is the largest indigenous ethnic group in Sarawak, Malaysia which made up of approximately one third of the total of Sarawak’s population. During the 20th century, the Iban society had gone through a state of flux where people have to readapt themselves in meeting the demanding challenges of Malaysian nationalism. Drawing upon Barendregt's (2014) 'alternative conceptions of modernity' this paper examines how the Iban reference both a national as well as a local music industry particularly through their use of language as an expression of Iban. As seen in Iban popular music, which are created and used as a propaganda tool for national building. First the paper will examine the meaning of modernity. Then, combining the concept of modernity and historiography methods, tracing the history of Sarawak in analysing the the Iban song lyrics. Hence, the aim of this paper is to interpret the meaning of the lyrics and how the song lyrics in ‘Malaysia Baru’ responded to modernity in the history of Sarawak. This reflects how the Iban people responded to the modernity through the historical processes on the social, cultural, physical, economic and political environments in Sarawak.